2018
DOI: 10.1002/adfm.201706690
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Organic/PbS Quantum Dot Bilayer Photodetector with Low Dark Current and High Detectivity

Abstract: Owing to their ease of fabrication, low cost, and high flexibility, organic materials have attracted great interests in photodetector (PD) applications. However, suffering from large dark current, small photocurrent, low on–off ratio, and low sensitivity, performances of bare organic‐based PDs are not satisfactory. Integrating organic materials with other novel semiconductor materials offers an opportunity to overcome these drawbacks. Here, a lateral hybrid organic/lead sulfide (PbS) quantum dot bilayer PD is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
144
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 53 publications
2
144
0
Order By: Relevance
“…Compared to inorganic photodetectors, the OPDs usually exhibit relatively slow response speed, which can be typically attributed to i) the organic semiconductor materials with low charge carrier mobility, and ii) the rather long RC‐time in these devices since the junctions are normally very thin and therefore they have high capacitance . In the future, by combining the advantages of both organic semiconductor materials (facile solution processing) and inorganic semiconductor materials (high charge carrier mobility), the organic–inorganic hybrid photodetectors are expected to achieve special wavelength detection and exhibit excellent performance . In addition, the multifunctional OPDs can overcome the limitation of single functional model and meet the need of versatility in practical application, extending their application filed .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to inorganic photodetectors, the OPDs usually exhibit relatively slow response speed, which can be typically attributed to i) the organic semiconductor materials with low charge carrier mobility, and ii) the rather long RC‐time in these devices since the junctions are normally very thin and therefore they have high capacitance . In the future, by combining the advantages of both organic semiconductor materials (facile solution processing) and inorganic semiconductor materials (high charge carrier mobility), the organic–inorganic hybrid photodetectors are expected to achieve special wavelength detection and exhibit excellent performance . In addition, the multifunctional OPDs can overcome the limitation of single functional model and meet the need of versatility in practical application, extending their application filed .…”
Section: Introductionmentioning
confidence: 99%
“…By using femtosecond transient absorption spectroscopy, they confirmed that there was efficient charge transfer between the MoS 2 and the g‐C 3 N 4 . Wei et al fabricated hybrid bilayer PDs constructed from a PbS QDs film and an organic blend film which was composed of poly[(2,6‐(4,8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1,2‐b:4,5‐b′]dithiophene))‐ alt ‐(5,5‐(1′,3′‐di‐2‐thienyl‐5′,7′‐bis(2‐ethylhexyl)benzo[1′,2'‐c:4′,5′‐c′]dithiophene‐4,8‐dione))] (PBDB‐T) as donor and the porphyrin molecule PBI‐Por as acceptor (see Figure e,f) . Benefiting from the well‐aligned energy levels, the photogenerated electrons and holes could be transported separately, leading to high I p , and the depletion region formed by the two layers would reduce I d .…”
Section: Performance Improvement Strategiesmentioning
confidence: 99%
“…Copyright 2016, American Chemical Society. e,f) Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Performance Improvement Strategiesmentioning
confidence: 99%
“…Colloidal quantum dots (QDs) made from lead chalcogenides, such as PbSe and PbS, have been extensively used in photodetectors, field effect transistors, light emitting devices (LEDs), and photovoltaic cells . The remarkable versatility of these QDs derives from their bandgap tunability through size control, facile modification of physical properties via surface engineering, and ability to achieve efficient multiple exciton generation .…”
Section: Introductionmentioning
confidence: 99%